La gestión áulica en el proceso didáctico - Morales Cuasquer, Odalis Paola (2022)
Nowadays, Classroom Management is fundamental in the professional and academic development of teachers and students, since it helps to create a motivating and active work environment, allowing the teacher to use didactic strategies in order to promote meaningful learning. However, the teacher's lack of knowledge about classroom management in the didactic process has produced disinterest in learning among students because teaching replicates the traditional model, leaving the student as a passive being and receiver of knowledge. Therefore, the objective of this research is to improve classroom management through guidelines to strengthen the didactic process of students in 5th grade of elementary education of Jorge Icaza High school, Latacunga canton, province of Cotopaxi, year 2021. The Methodology of this project was based on Qualitative research, because it allowed to enter into the reality of the educational context to observe the environment where teachers and students develop, the method used was Inductive with descriptive and documentary or Bibliographic research, the data were obtained through the technique of Observation, with its Observation guide instrument, to collect information and relevant data of the subject to investigate. The result of this research work are guidelines that generate changes in classroom management within the didactic process, such as: communication in the classroom, interaction, body language, design of the physical environment of the classroom, use of the blackboard, motivation, discipline and classroom control, where the description, usefulness and different guidelines are found to achieve a good classroom environment and to apply them at the time of teaching a class. Thereby, the research project contributes to strengthen the teacher's performance within the classroom management allowing to improve the teaching process in an active way, motivating students to obtain a significant learning, breaking the traditional schemes, with the purpose that the teacher is only the guide of knowledge.